Viral loads : anthropologies of urgency in the time of COVID-19 - Manderson, Lenore; Burke, Nancy Jean; Wahlberg, Ayo (Embodying inequalities., 2021)
Viral Loads provides a global response to the COVID-19 pandemic from the field of medical anthropology.